Circular RNAs in heart failure. (27th March 2017) - Devaux, Yvan; Creemers, Esther E.; Boon, Reinier A.; Werfel, Stanislas; Thum, Thomas; Engelhardt, Stefan; Dimmeler, Stefanie; Squire, Iain; ,
Abstract: Cardiovascular disease, and particularly heart failure, is still a serious health care issue for which novel treatments and biomarkers are needed. The RNA family comprises different subgroups, among which the small‐sized microRNAs and the larger long non‐coding RNAs have shown some potential to aid in moving personalized health care of heart failure patients a step forward. Here, members of the Cardiolinc network review the recent findings suggesting that the less well‐known circular RNAs may constitute a novel reservoir of therapeutic targets and biomarkers of heart failure. The knowledge of the mode of biogenesis of circular RNAs will first be reported, followed by a description of different features that make these RNA molecules of interest for the heart failure community. The functions of circular RNAs in the heart will be described, with some emphasis given to their regulation in the failing heart. Circulating in the bloodstream, circular RNAs have appeared as potential biomarkers and recent findings associated with the use of circular RNAs as heart failure biomarkers will be discussed. Finally, some directions for future research will be provided.